Normal cardiac contraction in mice lacking the proline-alanine rich region and C1 domain of cardiac myosin binding protein C - Dijk, Sabine J. van; Witt, Christian; Harris, Samantha (Journal of molecular and cellular cardiology, 2015)
Cardiac myosin binding protein C (cMyBP-C) is an essential regulator of cross bridge cycling. Through mechanisms that are incompletely understood the N-terminal domains (NTDs) of cMyBP-C can activate contraction even in the absence of calcium and can also inhibit cross bridge kinetics in the presence of calcium. In vitro studies indicated that the proline-alanine rich (p/a) region and C1 domain are involved in these processes, although effects were greater using human proteins compared to murine proteins (Shaffer et al. J Biomed Biotechnol 2010, 2010: 789798). We hypothesized that the p/a and C1 region are critical for the timing of contraction. In this study we tested this hypothesis using a mouse model lacking the p/a and C1 region (p/a-C1−/− mice) to investigate the in vivo relevance of these regions on cardiac performance. Surprisingly, hearts of adult p/a-C1−/− mice functioned normally both on a cellular and whole organ level. Force measurements in permeabilized cardiomyocytes from adult p/a-C1−/− mice and wild type (Wt) littermate controls demonstrated similar rates of force redevelopment both at submaximal and maximal activation. Maximal and passive force and calcium sensitivity of force were comparable between groups as well. Echocardiograms showed normal isovolumetric contraction times, fractional shortening and ejection fraction, indicating proper systolic function in p/a-C1−/− mouse hearts. p/a-C1−/− mice showed a slight but significant reduction in isovolumetric relaxation time compared to Wt littermates, yet this difference disappeared in older mice (7-8months of age). Moreover, stroke volume was preserved in p/a-C1−/− mice, corroborating sufficient time for normal filling of the heart. Overall, the hearts of p/a-C1−/− mice showed no signs of dysfunction even after chronic stress with an adrenergic agonist. Together, these results indicate that the p/a region and the C1 domain of cMyBP-C are not critical for normal cardiac contraction in mice and that these domains have little if any impact on cross bridge kinetics in mice. These results thus contrast with in vitro studies utilizing proteins encoding the human p/a region and C1 domain. More detailed insight in how individual domains of cMyBP-C function and interact, across species and over the wide spectrum of conditions in which the heart has to function, will be essential to a better understanding of how cMyBP-C tunes cardiac contraction.
Gesehen am 10.01.2018